The Clinicopathological Distinction Between Seropositive and Seronegative Immune-Mediated Necrotizing Myopathy in China - Ma, Xue; Xu, Li; Ji, Suqiong; Li, Yue; Bu, Bitao (Frontiers in Neurology, 2021)
Objectives To compare the clinic-pathological features of patients with seronegative immune-mediated necrotizing myopathy (IMNM) and those positive for anti-signal recognition particle (SRP) or anti-3-hydroxy-3-methylglutarylcoenzyme-a reductase (HMGCR) antibodies. Methods We retrospectively analyzed the data of patients with IMNM from Neurology Department at Tongji Hospital from January 1, 2013, to December 31, 2019. Results Among the 117 patients with IMNM, 30.8% (36/117) were positive for anti-SRP antibodies, 6.0% (7/117) were positive for anti-HMGCR antibodies, and 13.7% (16/117) were seronegative. Myalgia at presentation (62.5% vs. 23.3%, p=0.0114) was more commonly observed in patients with seronegative IMNM than in those with seropositive IMNM. Subclinical cardiac involvement was also more frequently detected in seronegative IMNM than in seropositive IMNM (6/13 vs. 5/33, p= 0.0509, echocardiogram; 7/7 vs 12/24, p=0.0261, cardiac MRI). Deposition of membrane attack complex (MAC) on sarcolemma of myofibers in biopsied muscle was less commonly observed in patients with seronegative IMNM than in patients with seropositive IMNM (16.7% vs. 68.2% , p=0.0104). The rate of marked improvement following immunotherapy tended to be higher in patients with seronegative IMNM than in those with seropositive IMNM (87.5% vs. 61%, p=0.0641). Conclusions Patients with seronegative IMNM more frequently present with myalgia at onset, exhibit more subclinical cardiac involvement, uncommon MAC deposition on myofibers, and experience better outcomes than those with seropositive IMNM.